Epinephrine inaccessibility in Pakistan: potential health risks in a resource-limited economy - Maryyam Yousuf; Alina Naveed; Mehreen Kamran (Journal of the Pakistan Medical Association, 2026)
Dear Editor, Allergic diseases and the rising incidence of anaphylaxis are becoming a global burden, to which Pakistan is no exception. We are wish to highlight the need for thorough diagnostic evaluations, health education, improved treatment accessto treatment, and holistic health interventions. Major contributing factors include increasing urbanisation, lack of counselling, and nutritional mismanagement. Common allergens include pollen, dust mites, nuts, seafood, insect stings, and various medications. However, many patients remainunaware of their illness, and often confuse allergic reactions with infections or colds. The diagnostic gap is particularly pronounced in disadvantaged and rural areas, where access to allergy specialists and immunological diagnostic assays, such as skin prick and specific IgE testing, is limited. Anaphylaxis, a severe and life-threatening reaction, is poorly recognised and inadequately managed. According to one retrospective study of an anaphylaxis allergy clinic in a tertiary-care hospital in Karachi, only 22.5% of patients were given epinephrine as a first-line therapy [1]. The WAO Anaphylaxis Guidance 2020 stressed the role of epinephrine auto-injectors (EAIs) for pre-emptive use for those at risk and strongly recommends the early use of epinephrine [2]. However, based on personal experience, no EAIs were available even in a tertiary-care hospital in the capital of Pakistan, Islamabad. Severe financial constraints and limited supply chains make EAI access is almost impossible in Pakistan. Access to epinephrine, including cost-effective options like pre-filled syringes and EAI kits, is limited, with availability and user comprehension notably lacking [3]. Research from other countries also highlights the stark disparities in EAI supply, requiring resolution of economic and logistical roadblocks [4]. In mitigate this growing problem, allergy education should be integrated into primary healthcare training to improve early diagnosis and testing. Revise the healthcare policies governing the use of epinephrine so that it can be obtained easily and at little cost. Addisionally, schools should be encouraged to implement allergy management initiatives and public health campaigns to raise awareness and equip patients and caregivers adequately. Pakistan's health system must adapt to the rising burden of allergic diseases. Allergy-related morbidity and mortality will be reduced by enhancing provider and public awareness and providing access to life-saving medications.